Eradicating hepatitis C: The need for a public health response. Issue 9 (2nd September 2018) - Wallace, Jack; Richmond, Jacqueline; Ellard, Jeanne; Power, Jennifer; Lucke, Jayne
ABSTRACT: Hepatitis C is a global public health issue affecting 150–170 million people worldwide, and over 227, 000 Australians with an increasing morbidity resulting from the infection. The Australian Government funded access through the national health scheme to Direct Acting Antiviral (DAA) medication for all people with hepatitis C, regardless of disease staging or mode of transmission to eradicate hepatitis C in Australia. The availability of these drugs not only alters the end result of hepatitis C treatment from that of sustained viral response to cure, but necessitates a refocusing of the public health response to hepatitis C. This project, conducted prior to this funding announcement, interviewed key stakeholders in Australia to investigate the potential impact of DAAs on individuals with hepatitis C and their public health implications. The findings include that while DAAs are revolutionary, there remains essential barriers to their uptake including stigma and discrimination, and a lack of attention to the systematic implementation of the cure.